Tempurung Kelapa Dan Bonggol Jagung Sebagai "Carrier" Dalam Formulasi Pestisida - Emmy Ratnawati (Jurnal Kimia dan Kemasan, 1991)
The important properties of non mineral carriers are sorptive capacity, hardness, partcle size,bulk density,dustiness and inert. It seems that granular corn cobs and granuiar walnut sells properties are suitable and can be used for granular and dust pesticide formulation.